Workplace sedentary behaviour and work-related quality of life among office workers - A., Farah Farhanah; Rasdi, Irniza; Zainal Abidin, Emilia; Syed Ismail, Sharifah Norkhadijah; Dusanee, Suwankhong (Universiti Putra Malaysia, 2022)
Work-related quality of life (WRQoL) plays an important role in maintaining workers’ performances and organization’s productivity. Advanced technology creates changes from paper-based work to computer-based which lead to sedentary behaviour (SB) during working life. This study aims to examine the association between SB and work factors with WRQoL among government office workers. Methods: This cross-sectional study involved 126 government office workers in Putrajaya who were randomly selected. Their age ranged between 20 - 60 years old. The adopted WRQoL questionnaire was used to assess their WRQoL while pedometer and OSPAQ were used to determine SB. Results: Majority (69.8%) of the respondents were female, Malay (92.9%) and married (84.1%). About half (53.6%) of respondents reported to have high WRQoL. Only 9.5% of them claimed that they were dissatisfied with their WRQoL. Almost all respondents (95.5%) were classified as sedentary. The mean of steps taken per day was 2521.95 steps/day. 55.6% of respondents spent their time above average for sitting per day. SB did not have significant association with WRQoL. Instead, salary, educational level and job position were found to be significantly associated with WRQoL. In multiple regression, only educational level remains significant to predict WRQoL. Conclusion: More intervention strategies are needed to reduce workplace SB among office workers.